The characteristics of majority paddy farmers in Ketara, Terengganu - Zaini, Nurul Najwa (2016)
Rice is the most important food for Malaysians. The government has categorized this crop as a food security. Lack of rice production means shortages of staple food, and this could put the country in a less secure condition. To solve this problem, the government has developed eight granary areas as a national main production area. These areas have a good irrigation and effective management system for production of high performance of rice. However, the performance of the rice yield is still at the low level which is 5mt/ha, but there are four granary areas that produce more than national yield average which are IADA Northwest Selangor, IADA KETARA, IADA Penang, and MADA. The characteristic of farmers play a main role to adopt the technology. The objective for this study is to identify the characteristic of majority paddy farmers in KETARA, Terengganu. Besides that, the aim of this study is to determine the relationship between the characteristic of majority paddy farmers and their performance and to examine the most important characteristic that influenced the respondent’s performance. In addition, in this study we would like to know the willingness of majority paddy farmers to help the unsuccessful paddy farmers. This study was conducted in KETARA area that consists of 100 farmers as respondent who have average yield of 4 to 6mt/ha. All the data were analysed by using SPSS version 21.0 with descriptive, correlation and regression analysis techniques.